Morphologic and kinematic characteristics of elite sprinters - Coh, M.; Milanovic, D.; Kampmiller, T. (Collegium Antropologicum, 2001)
The purpose of the study was to ascertain the basic morphologic and kinematic characteristics of elite sprinters. The sample included 24 sprinters, with times over a 100 m distance between 10.21 s and 11.19 s. Morphologic characteristics of the sprinters were measured with a test battery of 17 measures, obtained according to the methodology prescribed by the International Biologic Programme (IBP). The kinematic variables were obtained from a flying start 20 m run and a 20 m run with a low start, with the technology of a contact carpet (ERGO TESTER-Bosco). Stride frequency and length, duration of contact and flight phases were registered. Time parameters were measured with a system of infrared photocells (BROWER Timing System). T-test showed that elite sprinters do not differ significantly in morphologic characteristics (p > 0.05) from the 100 m results point of view. However, statistically significant differences were obtained in starting acceleration and maximal velocity. The most important kinematic parameters for generating differences between the elite sprinters are contact time and stride frequency.